Kontribusi Dinas Syariat Islam Terhadap Penerapan Qanun Tentang Khalwat di Aceh - Abdullah Lawang, Karimuddin; Kholis, Nur; Tarwiyani, Tri; Kamal, Mustafa; Yasir, Muhammad; Abdullah, Asnawi (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2024)
Aceh is the only province in Indonesia that has officially implemented Islamic Sharia law. As A Region With Special Privileges To Enforce Sharia Law, Aceh Has Enacted Uqubat Punishments As An Effort To Reduce Criminal Acts, Including Khalwat (Intimate Proximity Between A Man And A Woman Who Are Not Mahram). This Study Aims To Explore The Implementation Of Uqubat Punishment For Khalwat Behavior In The Context Of Crime Prevention In Aceh. This Research Uses A Qualitative Method With Data Collection Techniques Through Interviews, Observations, And Documentation. Once All The Data Is Collected, It Will Be Analyzed Using Content Analysis Techniques. The Results Of The Study Indicate That The Enforcement Of Uqubat Punishment Has Had A Significant Impact On Reducing Criminal Acts, Including Khalwat Behavior. However, There Are Also Several Challenges In Its Implementation, Such As Issues Of Justice In The Application Of Uqubat, Its Effectiveness, And Others. Therefore, This Study Recommends The Need For A Comprehensive Evaluation Of The Implementation Of Uqubat Punishment As Well As Continuous Improvements In The Judicial System In Aceh To Ensure Its Effectiveness In Reducing Crime Without Violating Principles Of Justice. Â